Parasites of Cockroach Periplaneta americana (L.) in Al-Diwaniya province,Iraq. - S. Mahdi Al-Yaqoobi, Muhammed; M. Hamza Al-Mayali, Hadi (University of Thi-Qar Journal of Science, 2019)
Out of 150 cockroaches examined in this study, 125 cockroaches (83. 33%) were infected with one or several species of external parasites (33.3) or gastro-intestinal helminthes (80%). The percentage infection and number of parasites of Cockroaches trapped in the toilets of houses more than infection of cockroaches trapped from the kitchens of houses (100% and 50%respectively) and 2-62 parasites/ml of Cockroaches trapped in the toilets while those trapped from the kitchens was1- 28 parasites/ml houses. A seven species were isolated from the external surface and intestinal tract represented two protozoa and five nematodes. This species were: Entamoeba blatti (33%), Nyctotherus ovalis (65.3 %), Hammersmiditiella diesingi (33.3 %), Thelastoma bulhoe (51.4 %), Gordius robustus (Horsehair worm) (1.3%), Enterobius vermicularis eggs , (2%) Ascaris lumbricoids eggs (1.3%). No Cestodes were records in the study. Prevalence of intestinal worms was statistically higher significant than the protozoa in (P<0.05). The number of worms per cockroaches ranged from 1-3 while protozoa 42 parasites/ml. Prevalence of endoparasites were higher than ectoparasites and intestinal worms was statistically higher significant than the protozoa in (80%; 3. 3%) and (83. 3%; 65.3 %) respectively. This study revealed Cockroach represent an important reservoir or carrier for medical importance parasites of human in houses as Enterobius vermicularis and Ascaris lumbricoids . The work presents the first record of cockroach’s parasites in Al-Diwaniya.